2018
DOI: 10.1111/jocd.12754
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and antityrosinase activity of carvacrol, thymoquinone, and four essential oils of Lebanese plants

Abstract: Summary Objective In our study, we aim to explore the ability of four essential oils (EO) of Lebanese plants to inhibit the tyrosinase activity and to correlate their efficiency level to their phytochemical compositions. Methods The EO have been extracted by hydrodistillation using a Clevenger apparatus and have been studied by GC‐MS analysis. Active compounds of Origanum species were identified and antityrosinase activities of EO and active molecules (carvacrol and thymoquinone) have been tested in tubo. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Results showed that both O. syriacum oil and carvacrol inhibited the activity of tyrosinase without affecting the enzyme's level in B16-F1 melanocytes, suggesting that the extract reduces the level of melanin by blocking melanogenesis. This is in agreement with an earlier study, as O. syriacum essential oil at 40 µg/mL and carvacrol at 2.5 µg/mL were able to inhibit the activity of tyrosinase in tubo by 80% and 56%, respectively [35]. The proposed mechanism of action of the O. syriacum extract involves a competitive inhibition model whereby carvacrol binds to tyrosinase, preventing the binding of its usual substrate tyrosine in a mechanism similar to that involving the commonly used skin-lightening agent hydroquinone in the treatment of hyperpigmentation [76,79] as seen in Figure 6.…”
Section: Antimelanogenic Activitysupporting
confidence: 93%
See 2 more Smart Citations
“…Results showed that both O. syriacum oil and carvacrol inhibited the activity of tyrosinase without affecting the enzyme's level in B16-F1 melanocytes, suggesting that the extract reduces the level of melanin by blocking melanogenesis. This is in agreement with an earlier study, as O. syriacum essential oil at 40 µg/mL and carvacrol at 2.5 µg/mL were able to inhibit the activity of tyrosinase in tubo by 80% and 56%, respectively [35]. The proposed mechanism of action of the O. syriacum extract involves a competitive inhibition model whereby carvacrol binds to tyrosinase, preventing the binding of its usual substrate tyrosine in a mechanism similar to that involving the commonly used skin-lightening agent hydroquinone in the treatment of hyperpigmentation [76,79] as seen in Figure 6.…”
Section: Antimelanogenic Activitysupporting
confidence: 93%
“…This method of extraction requires the whole plant, d and shredded, to be fully immersed in water in a hydrodistillation Clevenger appar The mixture is then boiled for 3 h, and the essential oil is driven with water vapor in refrigerated tube, then recovered in a glass test tube and purified with anhydrous sod bicarbonate. Finally, it is stored in the dark at 4 °C in a sealed glass vessel [35]. In an a comparing the extracted oils obtained through conventional hydrodistillation or m wave-assisted hydrodistillation, results showed that microwave-assisted hydrodis tion was three times faster and required less time (around 10 min) to reach the requ temperature than the conventional method; moreover, the yield of the former was m greater than that of the latter, and the whole process took less time [36].…”
Section: Extraction Methods For Origanum Syriacummentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, 50 µL of L-tyrosine solution and 50 µL of tyrosinase solution were mixed with 50 µL of the aqueous fraction extracts or kojic acid solution. The mixture was incubated at 37 • C for 60 min, and the dopachrome was measured by UV-Vis spectroscopy at 475 nm [52]. Data are representative of three independent experiments.…”
Section: Antityrosinase Activitymentioning
confidence: 99%
“…Firstly, research backs up their efficacy as valuable cosmeceuticals. They have been shown to exhibit properties of antimicrobials [ 2 , 3 ], antioxidant agents [ 4 , 5 ], antityrosinase agents [ 6 , 7 , 8 ], sunscreens [ 9 , 10 ], natural preservatives [ 11 ], natural sources of fragrance [ 12 ], as well as inhibitors of skin’s degradation enzymes (collagenase and elastase) [ 13 ]. Secondly, the small lipophilic molecules that make up their composition grant easy penetration through the skin layers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%